Dams in the Mekong Basin: Commissioned, Under Construction and Planned Dams in May 2013 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Shows all known commissioned, under construction and planned dams in the Mekong River Basin as at May 2013.